Drug use in college students: a 13-year trend - Wagner, Gabriela Arantes; Oliveira, Lúcio Garcia de; Barroso, Lucia Pereira; Nishimura, Raphael; Ishihara, Luciana Morita; Stempliuk, Vladimir de Andrade; Duarte, Paulina do Carmo Arruda Vieira; Andrade, Arthur Guerra de (Revista de Saúde Pública, 2012)
OBJECTIVE: To analyze drug use trends among college students in 1996, 2001 and 2009. METHODS: A cross-sectional epidemiological study with a multistage stratified cluster sample with 9,974 college students was conducted in the city of São Paulo, southeastern Brazil. An anonymous self-administered questionnaire was used to collect information on drug use assessed in lifetime, the preceding 12 months and the preceding 30 days. The Bonferroni correction was used for multiple comparisons of drug use rates between surveys. RESULTS: There were changes in the lifetime use of tobacco and some other drugs (hallucinogens [6.1% to 8.8%], amphetamines [4.6% to 8.7%], and tranquilizers [5.7% to 8.2%]) from 1996 to 2009. Differences in the use of other drugs over the 12 months preceding the survey were also seen: reduced use of inhalants [9.0% to 4.8%] and increased use of amphetamines [2.4% to 4.8%]. There was a reduction in alcohol [72.9% to 62.1%], tobacco [21.3% to 17.2%] and marijuana [15.0% to 11.5%] use and an increase in amphetamine use [1.9% to 3.3%] in the preceeding 30 days. CONCLUSIONS: Over the 13-year study period, there was an increase in lifetime use of tobacco, hallucinogens, amphetamines, and tranquilizers. There was an increase in amphetamine use and a reduction in alcohol use during the preceding 12 months. There was an increase in amphetamine use during the preceding 30 days.